Processos de ensinar e de aprender: os instrutores militares e os cadetes da aeronáutica - Kirsch, Deise Becker (Universidade Federal de São Carlos, 2013)
This study was part of a Doctoral Course research, of the Post Graduate Program in Education, by the Federal University of São Carlos, and was developed at the Brazilian Air Force Academy (AFA) in the city of Pirassununga / SP. The research aimed to map the specificities of the military instructors teaching and learning process, regarding to the theoretical and practical concepts about the teaching, and the teaching and learning process of cadets at the Air Force Academy. Therefore, the research subjects were three military airmen instructors,graduatedby AFA, who taught classes in the AFA´s Division of Education; were also subjects of this study 78 cadets of the Aviation Course who, in 2012, were in the last year of the mentioned Course. The theoretical referenceof the work was composed by Libâneo studies (1994), regarding to traditional and technicistpedagogical trends, the role of teacher and student and the characteristics of the educational process in these conceptions. Mizukami (1986, 2002, 2004, 2005-2006) contributes towards to traditional, constructivist and technicistteaching, and discuss about the initial and continuing education, as well as details the processes of teaching and learning. About the construction of teacher identity, the contribution comes with Veiga (2010, 2011), Gatti (2011), Pimentaand Anastasiou (2011). The authors, as well as Gil (2009) refer to higher education, about giving classes, about being a teacher. Still, Zabala (1998) addresses the interaction in the classroom as fundamental for the growth of the students, also bringing consistent arguments about the conception of constructivist education. The teachingactivity as a work, the teacher´s knowledge and the professional development have theoretical basement in Tardif (2002, 2009). Processes of teaching at university, coined by Anastasiou and Alves (2003), is developed in this study. Finally, Shulman (1986, 2004, 2005) collaborates with its work on the knowledge base for teaching, pedagogical reasoning and also considers the reflective processes on that path. However, about thethinking aboutteaching practice, the ideas of Schön (1995, 2000) and Pérez Gómez (1995) are discussed. The methodology used in this study was a descriptiveanalytic one, based on data collected from open non-structured interviews, open semistructured interviews and questionnaires applied to the subjects. From the data analysis it was possible to comprehend that the military instructors have a very consistent specific training in their area, Aviation,while they don´t have preparation for teaching in military higher education and learn to be a teacher in pedagogical practice in the classroom . The responses of cadets confirmed this situation, and also demonstrated that their conceptions about the teaching, learning, the importance of interaction in the classroom, the didactics, the best and the worst teacher, are very close to the concepts of the military instructors. Therefore, the processes of teaching and learning are constructions that occur throughout the school experience, at any of the levels that the subject is inserted. In short, it demands work, knowledge and commitment by the teacher; and activity, study, dedication and interest by the student.
Keywords: Ensino; Educação militar; Ensino aprendizagem; Professores - formação; Professores e alunos; Formação do instrutor; Cadete da Aeronáutica; Military education; Teaching learning; Instructor´s formation; Air Force Cadet; CIENCIAS HUMANAS::EDUCACAO